An insight review of lignocellulosic materials as activated carbon precursor for textile wastewater treatment - Abu Bakar, Norshila; Othman, Norzila; Yunus, Zalilah Murni; Altowayti, Wahid Ali Hamood; Tahir, Muhammad; Fitriani, Nurina; Mohd Salleh, Siti Nor Aishah (ScienceDirect, 2021)
The huge quantities of textile industry effluents with high concentrations of heavy metals are associated with the water pollution. Among the conventional technologies currently in use for heavy metals removal, the adsorption offers an economical and ecofriendly approach for textile wastewater treatment. Adsorption efficiency is depending on the chemical structure of the adsorbent such as activated carbon from agricultural waste. Banana peel waste as activated carbon has been reported with high efficiency to remove heavy metals from the textile wastewater. The current review describes the impacts of heavy metals from textile industries on human, plants, and animals and the various methods used for the removal process. The paper looked into the various adsorption methods, and the methods used for generating activated carbon from the lignocellulosic materials. Moreover, the agricultural residues are lignocellulosic substances that encompass hemicelluloses, cellulose, and lignin which is denoted as the most stable in terms of thermal factor. The review works focus on lignocellulosic substances as an efficient adsorbent for heavy metals and colour (dyes) removal. It appeared that the adsorption capacity for different types of the biomass ranged from 153.85 to 7.24 mg g−1 for Cd2+ ions, 1067.8 to 18.9 mg g−1 for Cu2+ ions, 175.6 to 1.7 mg g−1 for Ni2+ ions, 566.4 to 7.23 mg g−1 for Pb2+ ions and from 534.2 to 0.45 mg g−1 for Zn2+ ions. These findings indicated that the heavy metals having different affinity to the adsorbent, among the heavy metals Ni2+ and Cd2+ has less affinity and the adsorbent used for the removal these metals need to be prepared with high porosity and surface area.